Healthcare Providers Face Numerous Challenges in Treating Patients with Psoriasis: Results from a Mixed-Methods Study. Issue 1 (January 2022) - Murray, Suzanne; Crowley, Jeffrey; Gooderham, Melinda J.; Kivitz, Alan; Chandran, Vinod; Péloquin, Sophie; Doghramji, Paul P.; Freeman, Christie; Lazure, Patrice
Background: The paradigm shift toward biologic medications in psoriasis care requires healthcare providers (HCPs) to become acquainted with mechanisms of action and safety profiles of these new treatments to confidently use them in practice. A better understanding of this paradigm shift is necessary to provide adequate education for HCPs in psoriasis care. Objectives: This study assessed clinical practice gaps and challenges experienced by HCPs caring for patients with psoriasis. Methods: A mixed-methods approach was used to identify practice gaps and clinical challenges of dermatologists, rheumatologists, primary care physicians, physician assistants, and nurse practitioners with various levels of clinical experience in academic and community-based settings. Qualitative and quantitative data were collected sequentially. Interviews were transcribed and thematically analyzed. Results: A total of 380 psoriasis care providers in Canada and the US participated in this study. Analysis revealed challenges in establishing an accurate diagnosis of psoriasis (including screening for sub-type and distinguishing psoriasis from other skin conditions), selecting treatment (particularly regarding recently approved treatments), monitoring side effects, and collaborating with other HCPs involved in psoriasis care. Conclusion: These findings highlight educational needs of HCPs involved in psoriasis care that could have repercussions on accurate and timely diagnosis of the condition, treatment initiation, side effect monitoring, and continuity of care. Findings provide a starting point for clinicians to reflect on their practice and for the improvement of continuing professional development interventions that would bridge these gaps.